2002
DOI: 10.1901/jaba.2002.35-349
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Activity Choice on Problem Behaviors Maintained by Escape Versus Attention

Abstract: This study assessed whether the function of an individual's problem behavior was related to the effectiveness of an intervention involving choice among tasks. Analogue functional analyses were conducted with 7 students with various diagnoses to determine whether problem behaviors were maintained by escape or attention. Following identification of the function of each student's problem behavior, reversal designs were used to assess the effectiveness of an intervention that allowed the students to choose their o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 24 publications
2
72
0
1
Order By: Relevance
“…Several experimental studies have also included choice-making as a major component in successful behavior support plans (Dunlap, Kern-Dunlap, Clarke, & Robbins, 1991; Lindauer, Deleon, & Fisher, 1999). Research findings also suggest that giving students opportunities to choose among several tasks can decrease the likelihood of escape-motivated behavior (Romaniuk et al, 2002).…”
Section: Introductionmentioning
confidence: 92%
“…Several experimental studies have also included choice-making as a major component in successful behavior support plans (Dunlap, Kern-Dunlap, Clarke, & Robbins, 1991; Lindauer, Deleon, & Fisher, 1999). Research findings also suggest that giving students opportunities to choose among several tasks can decrease the likelihood of escape-motivated behavior (Romaniuk et al, 2002).…”
Section: Introductionmentioning
confidence: 92%
“…Providing choices to individuals with disabilities has been encouraged within interventions as a means to develop autonomy as well as being an important part of the normalization process (Fisher, Thompson, Piazza, Crosland, & Gotjen, 1997). A number of investigations have shown that allowing individuals to make choices between tasks or reinforcing consequences is an effective technique in both decreasing maladaptive behavior and increasing compliance to instructions (Powell & Nelson, 1997;Romaniuk et al, 2002).…”
Section: Choice Proceduresmentioning
confidence: 99%
“…In a study conducted by Romaniuk et al (2002), they evaluated the effects of providing a choice among tasks on problem behavior maintained by social positive and social negative reinforcement within a reversal design. The functional analyses of seven participants with various diagnoses revealed that three children engaged in behaviors maintained by social-positive reinforcement, three others demonstrated behaviors maintained by social-negative reinforcement, while the last child's behavior was identified as being multiply controlled by both sources of reinforcement.…”
Section: Choice Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Lerman et al [2] found that the opportunity for making a choice appears to be beneficial for these individuals. Romaniuk et al [3] reported that individuals who display challenging behaviours often exhibit these when they are given opportunities to make choices, thus demonstrating a stimulus preference.…”
Section: Introductionmentioning
confidence: 99%